Therapeutic Choirs for Families Living with Dementia: A Phenomenological Study. Issue 1 (2nd January 2023) - Thompson, Zara; Tamplin, Jeanette; Clark, Imogen; Baker, Felicity
ABSTRACT: This paper seeks to represent the perspectives of community-dwelling people who are living with dementia and their family care-partners, who participated community-based, therapeutic choirs that were formed as part of the Remini-Sing project. Interpretative Phenomenological Analysis (IPA) was used to analyze data from interviews with fourteen participants (7 people living with dementia [4 women, mean age = 82] and 7 care-partners [5 women, mean age = 68]). Eight themes identified the perceived benefits of choir singing and elements of the choirs and research project more broadly that influenced participation. Findings support past research that suggests choir singing is an accessible and enjoyable activity that can support the health and wellbeing of people living with dementia and their family care-partners. Challenges with recruitment and sustainability of programs post-research are highlighted.